2016
DOI: 10.1210/jc.2016-2348
|View full text |Cite
|
Sign up to set email alerts
|

Independent Contributions of Nocturnal Hot Flashes and Sleep Disturbance to Depression in Estrogen-Deprived Women

Abstract: Depressive symptoms emerged after estradiol withdrawal in association with objectively and subjectively measured sleep disturbance and the number of nighttime, but not daytime, HFs reported. Results suggest that sleep disruption and perceived nighttime HFs both contribute to vulnerability to menopause-associated depressive symptoms in hypoestrogenic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…Results from a clinical trial further show independence of HFs, mood, and sleep: Joffe et al 120 found that increasing estradiol (in perimenopausal women) and improved sleep quality (in peri/postmenopausal women) predicted improved mood, but reduced HFs did not. To further investigate the interdependency between sleep, HFs, and mood, Joffe et al 121 conducted an experimental study that induced HFs in healthy nonmenopausal women. They found that PSG-measured sleep and nighttime HFs independently predicted mood deterioration.…”
Section: Sleep and Mood Disturbance In The Menopausal Transitionmentioning
confidence: 99%
“…Results from a clinical trial further show independence of HFs, mood, and sleep: Joffe et al 120 found that increasing estradiol (in perimenopausal women) and improved sleep quality (in peri/postmenopausal women) predicted improved mood, but reduced HFs did not. To further investigate the interdependency between sleep, HFs, and mood, Joffe et al 121 conducted an experimental study that induced HFs in healthy nonmenopausal women. They found that PSG-measured sleep and nighttime HFs independently predicted mood deterioration.…”
Section: Sleep and Mood Disturbance In The Menopausal Transitionmentioning
confidence: 99%
“…Many studies have reported that the major factors influencing the occurrence of depressive symptoms in menopausal women include menopause, hot flashes, sweating, and endocrine factors. 15 , 16 , 29 Gibson et al reported that depressive symptoms are more likely to occur in women at early perimenopause than in women at late perimenopause. 15 Berent-Spillson et al reported that endocrine and metabolic factors play a significant role in enhancing the risk of depressive symptoms in menopausal women.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Joffe et al employed a gonadotropin-releasing hormone agonist-based experimental model, compared the experimental groups with the control groups, and found that the depressive symptoms in menopausal women were affected by hot flashes, sweating, and night-time sleep interruption. 16 However, these studies failed to employ a quantitative index to compare the risks of depressive symptoms at different menopausal stages; also, they did not analyze and predict the risk ratio for important factors such as hot flashes and sweating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That claim has been put forward by various authors of original studies (e.g., Bromberger et al, 2011; Joffe et al, 2016) and narrative reviews (e.g., Freeman, 2010; Soares, 2010). For instance, Bromberger et al (2011) stressed that “we have moved from the “belief” that women were particularly susceptible to depression after the menopausal transition to the current empirically supported conclusion that middle-aged women are at a greater risk for depression during the transition than before [references]” (p. 1879).…”
Section: First Claim: the Transition To Menopause Increases The Risk mentioning
confidence: 91%